Adoption of improved sesame varieties in Meisso District, West Hararghe Zone, Ethiopia - Gedefa, B. (Haramaya University, 2010)
Achieving national food security and diversifying export earning agricultural commodity is one of the major challenges currently facing developing countries like Ethiopia. Oils crop in general and sesame crop in particular play a great role in improving household’s food security, increasing income for the local population and export earnings for the country. Despite the high production potential and the economic importance of the crop, sesame producers particularly small scale farmers did not economically much benefited from its production. Low production and productivity, which is mainly associated with poor adoption of improved technologies and poor marketing system, was among the major problems. To this end, the objectives of this study were: to assess the relative financial profitability of improved sesame varieties, to assess the perception of farmers about improved sesame varieties attributes and to explore the contribution of farmer-to-farmer knowledge sharing to adoption decision and finally to determine the relative importance of the various factors associated with adoption of improved sesame varieties. For this study, a three stage of sampling procedure was employed to select the sample households. First, Meisso district was purposively selected. At the second stage, four PAs were randomly selected among sesame growers PAs using random sampling method. Finally, 140 sample respondents were selected from the sampling frame based on probability proportional to size of sesame growers (PPS) random sampling method. In this study, data were obtained from 140 randomly selected households through personal interview conducted by trained enumerators using pre-tested interview schedule and from group and individual discussions, as well as the researcher’s personal observations. In addition, secondary data were collected from relevant sources such as research, zonal and district office of agriculture and others. In order to describe and compare different categories of the sample units with respect to the desired characteristics, mean, standard deviation and percentage were computed. Furthermore, chi-square and an independent sample t-test were used to identify variables that vary significantly between adopters and non-adopter.Logistic regression (binary logit) analysis was used to identify the relative importance of the various factors associated with adoption of improved sesame varieties. The economic analysis using the partial budgeting method and price sensitivity analysis was also used to ascertain the profitability of the adopted improved sesame technologies. The result of the study indicated that about 42.9% of the sample respondents were adopters of the improved sesame varieties, while 57.1 % non- adopters.The survey result also revealed that knowledge/information from farmer to farmer knowledge sharing at their work and market place was found to exert a significant impact on the probability of improved sesame varieties adoption by farmers. This was due to the farmers perceived that the information is most relevant, trusted and frequently accessible for the farmers decision making to adopt improved sesame technology. Innovative farmers are not only as source of knowledge of technology but also they are the source of improved seed for the majority of the adopters in the study area.Results of the logistic regression analysis indicate that among ,18 xvi identified explanatory variables nine of them significantly influenced adoption of improved sesame varieties.Education,sex, family labor supply, livestock onwership,total farm income earned ,perception on varieties attributes, farmer to farmers knowledge sharing and experience in sesame crop production have associated singificantly and positively with adoption of improved sesame varieties.whereas,distance from market center has associated significantly but negatively. The partial budget results also indicate that improved sesame varieties was highly profitable as against local cultivars sesame .The overall finding of the study underlined the high importance of institutional support in the areas of extension service to insist farmer-to-farmer knowledge sharing and market to enhance adoption of improved sesame varieties. There is also need to consider farmers’ views during the new sesame technology development, evaluation and dissemination process because farmer views help scientists to design, test and recommend new technologies in light of information about farmers’ criteria for usefulness of the innovation. Moreover, due attention and policy consideration has to be given by government to those significant variables which have a potential impact in determining farmer’s adoption decision in the study area.